Management of iatrogenic urethral foreign body after mid-urethral sling: A literature review - Bazinet, Amélie; Weis, Sylvia; Madec, François-Xavier; Boillot, Bernard (Canadian Urological Association Journal, 2023)
INTRODUCTION: Urethral mesh perforation is a rare complication of mid-urethral sling resulting in a lack of clear management guidelines. Thus, we aimed to determine management options and their respective outcomes in terms of erosion resolution and continence. METHODS: A literature review was performed by extracting studies from the PubMed, Cochrane, and Google Scholar from January 1996 to December 1, 2022. Only French and English language studies were included. A total of 227 papers were screened and assessed for eligibility. RESULTS: Forty-eight studies were included in the final analysis, for a total of 224 patients. Treatment options consisted of conservative, endoscopic, transurethral, and transvaginal approaches. Conservative treatment was associated with a 100% risk of persistence or recurrence of urethral perforation, while the failure rates for endoscopic, transurethral, and transvaginal approaches were 33%, 7.5%, and 7%, respectively. Most patients suffered from stress urinary incontinence after reconstructive management. The most common symptoms at the time of presentation were overactive bladder and pain. The mean time between the onset of symptoms and diagnosis was 10 months. About half of the urethral mesh perforations were diagnosed within the first years after the initial sling insertion. CONCLUSIONS: Multiple management options for sling penetration of the urethra have been described in the literature. Transvaginal sling resection with consecutive tissue interposition seems to carry the lowest risk of erosion recurrence; however, all treatment options are associated with a high relapse rate for stress urinary incontinence.